Pengaruh DER, ROE, SG, NPM, CR, DPR terhadap Nilai Perusahaan Sektor Industri yang terdaftar di BEI - Bayu Wulandari; Albert Albert; Feren Harianto; Sovi Sovi (Politeknik Ganesha Medan, 2021)
The purpose of this study was to see and test whether the effect of DER, ROE, Sales Growth, NPM, CR, Dividend Policy (DPR) on firm value (PBV) in consumer goods industry sector companies listed on the IDX (Indonesia Stock Exchange) year 2017-2019. This research uses a method with a quantitative descriptive approach. The population obtained was 51 companies listed on the IDX (Indonesia Stock Exchange) from 2017-2019. Samples were taken using the purposive sampling technique. This technique is also often used by other researchers because the samples obtained are closer to the research objectives. The samples obtained were 20 companies. Data analysis used several analyzes, namely multiple linear analysis, the coefficient of determination test, classical assumption test, F test, and t-test. This study shows positive results, that is, if seen partially, this research shows that the DER, ROE, Sales Growth, NPM, CR variables have no effect on the Firm Value variable. Variable Dividend Policy shows that the opposite result and significant effect on the variable value of the company (PBV) listed on IDX (Indonesia Stock Exchange). Variable DER, ROE, Sales Growth, NPM, CR, Dividend Policy (DPR) simultaneously affect the Company's variable value (PBV) in the company consumer goods listed on IDX (Indonesia Stock Exchange).